Liver stiffness measurements in chronic hepatitis C: Treatment evaluation and risk assessment. Issue 5 (7th December 2018) - Nakagomi, Ryo; Tateishi, Ryosuke; Masuzaki, Ryota; Soroida, Yoko; Iwai, Tomomi; Kondo, Mayuko; Fujiwara, Naoto; Sato, Masaya; Minami, Tatsuya; Uchino, Koji; Enooku, Kenichiro; Nakagawa, Hayato; et al.
Abstract: Background and Aim: Liver stiffness (LS), measured by transient elastography, has been validated as a non‐invasive surrogate for liver fibrosis. Methods: We investigated the long‐term predictive ability of LS for hepatocellular carcinoma (HCC) development and overall survival in 1146 patients with chronic hepatitis C by using LS value at enrollment. We also investigated chronological changes in LS based on antiviral therapy and its outcome in 752 patients. Results: During the mean follow‐up period of 6.6 years, 190 patients developed HCC. Cumulative HCC incidence rates at 5 years were clearly stratified as 1.7% in the ≤ 5 kPa, 3.3% in 5.1–10 kPa, 16.7% in 10.1–15 kPa, 24.4% in 15.1–20 kPa, 36.3% in 20.1–25 kPa, and 43.7% in > 25 kPa subgroups ( P  < 0.001). Overall survival was also stratified: 10‐year survival rates were 99.3% in the ≤ 5 kPa, 95.4% in 5.1–10 kPa, 81.4% in 10.1–15 kPa, 79.5% in 15.1–20 kPa, 66.1% in 20.1–25 kPa, and 49.1% in > 25 kPa subgroups ( P  < 0.001). LS decreased at a rate of 8.1% per year in those who achieved sustained virological responses, but increased at 0.1% per year in those who could not achieve sustained virological response instead of antiviral therapy, and increased at 3.7% per year in those who did not undergo antiviral therapy. Conclusions: Liver stiffness measurements can be useful in the prediction of HCC development and overall survival and in the evaluation of chronological changes in liver fibrosis grade during and after antiviral therapy.